Safety and Effectiveness of Hyaluronic Acid Filler, VYC-20L, via Cannula for Cheek Augmentation: A Randomized, Single-Blind, Controlled Study. Issue 12 (29th December 2021) - Jones, Derek; Palm, Melanie; Cox, Sue Ellen; McDermott, Michelle; Sartor, Marta; Chawla, Smita
Abstract : Supplemental Digital Content is Available in the Text. Abstract : BACKGROUND: Using cannulas to deliver facial fillers may reduce adverse events (AEs) compared with needle injection. OBJECTIVE: To evaluate the safety and effectiveness of VYC-20L (20 mg/mL hyaluronic acid gel with lidocaine) via cannula for midface age-related volume deficit. MATERIALS AND METHODS: This multicenter, evaluator-blind, randomized, within-subject, controlled study enrolled adults with moderate to severe Mid-Face Volume Deficit Scale (MFVDS) scores. VYC-20L was administered in one cheek via cannula (with optional needle use in the zygomaticomalar region) and in the other cheek via needle. The primary effectiveness end point was the mean (95% confidence interval [CI]) paired difference between treatments in MFVDS score change from baseline to Month 1; an upper CI limit of less than 0.5 determined noninferiority. Injection-site responses (ISRs), procedural pain, and AEs were assessed. RESULTS: Of 60 randomized and treated subjects, the mean change in MFVDS score from baseline to Month 1 was −1.8 with cannulas and −1.9 with needles, providing a mean (95% CI) paired difference of 0.1 (−0.05 to 0.25). Most ISRs were mild/moderate and resolved within 2 weeks. Procedural pain was minimal, and no serious AEs were reported. CONCLUSION: VYC-20L for cheek augmentation was safe and effective using a cannula and noninferior to needle injection.